2015
DOI: 10.3923/jm.2015.336.342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pregnant Women Susceptible to Cytomegalovirus Infection in Maiduguri, Nigeria

Abstract: Cytomegalovirus (CMV) screening in pregnancy has not been recommended during antenatal clinic days in Nigeria and most countries of the world. However, CMV has been widely accepted as, the viral etiology with the greatest propensity for congenital transmission. Due to CMV ubiquity, seronegative women are highly susceptible to CMV infection and thus, has increased risk of maternal infections and possibly congenital transmission. In view of this, this study aimed to determine the seroprevalence of women, who are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results of Nasir et al . 's[ 25 ] study in Nigeria showed that CMV seropositivity decreases significantly with the level of education. Hamdan et al .…”
Section: Discussionmentioning
confidence: 99%
“…The results of Nasir et al . 's[ 25 ] study in Nigeria showed that CMV seropositivity decreases significantly with the level of education. Hamdan et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the Yemen research, the majority of respondents were illiterate, but there were no statistically significant differences between those of the CMV seropositive and those with low education (12). While research in Nigeria has shown that the degree of seronegativity in CMV increases significantly with the level of education (26).…”
Section: Discussionmentioning
confidence: 99%